Zmiana kwalifikacji prawnej czynu w polskim procesie karnym - Zając-Bange, Iwona (My University, 2013)
Przedmiotem rozprawy doktorskiej jest problematyka zmiany kwalifikacji prawnej czynu w polskim procesie karnym. Przeprowadzone rozważania ukazały złożoność i doniosłość problematyki związanej ze zmianą kwalifikacji prawnej czynu w procesie karnym i to we wszystkich analizowanych aspektach, począwszy od problemów terminologicznych oraz związanych ze znaczeniem kwalifikacji prawnej czynu, po zasadnicze z punktu widzenia toku i celów procesu karnego zagadnienia odnoszące się do obowiązku zmiany kwalifikacji prawnej na poszczególnych etapach postępowania oraz uprawnień stron procesu do znajomości aktualnej oceny prawnej czynu. Poczynione ustalenia mają znaczenie nie tylko teoretyczne, ale również praktyczne, albowiem niemal w każdej sprawie karnej występuje zagadnienie dokonania prawidłowej kwalifikacji prawnej czynu i ewentualnej jej zmiany.

The subject of this doctoral thesis is the modification of the legal classification of an act in the polish criminal procedure. The dissertation depicts the complexity and significance of the issues connected with the modification of the legal classification of an act in criminal procedure in all analyzed aspects, beginning with terminological problems as well as the meaning of the legal classification of an act and going on with the issues of the obligation to modify the legal classification of an act during the individual phases of the proceeding and the right of the parties to know the current legal classification of the act, which are fundamental from the point of view of the course and the goals of the criminal trial. The findings have not only a theoretical but also a practical significance, since in nearly every case the question of determining the right legal classification of an act and modifying it if necessary arises.
Modification of the legal classification of an act in the polish criminal procedure
Wydział Prawa i Administracji
Keywords: postępowanie karne; criminal proceedings; kwalifikacja prawna czynu; legal classification of an act; zmiana kwalifikacji prawnej czynu; modification of the legal classification of an act